Exploration of factors affecting prognosis of stroke preceded by transient ischemic attack - Adly, Nermien; Ali, Safaa Hussein (Asian Journal of Medical Sciences, 2016)
Background: Age is the most important risk factor for stroke. The regional brain affection was not considered in a comparison between different brain locations as a predictor for outcome in those with and without prior TIA. Aims and Objectives: Can transient Ischemic attack predict stroke prognosis? Materials and Methods: Fifty nine patients, aged ≥ 55 years old, with recent ischemic stroke were studied, with (cases, 40.68%) and without (controls) antecedent TIA. National Institutes of Health Stroke Scale (NIHSS), modified Rankin scale (MRS), and California risk score (CRS) were assessed. A brain computed tomography was done. Results: Older age was a predictor of more severe stroke (P<0.001). Different latencies for TIA were studied. With reference to our controls, better prognosis was found only in cases with TIA ≤ seven days as a predictor for better NIHSS and MRS. In cases, CRS was a significant predictor of shorter latency. Infratentorial ischemic stroke, not supratentorial ischemic stroke, with prior TIA, was a significant predictor of lower NIHSS. Conclusion: TIA ≤ seven days is a predictor for better NIHSS and MRS. Asian Journal of Medical Sciences Vol.7(4) 2016 68-74